UJI PSIKOMOTOR WAKTU REAKSI PADA SISWA YANG SARAPAN DAN TIDAK SARAPAN - Rosita Andriani; Bambang Purwanto; Merryana Adriani (Amerta Nutrition, 2019)
Background: Eating habits that are currently owned by elementary school age children are difficult to eat with amoung should be three times a day according to the needs, one of them is breakfast. When they didn’t breakfast before went to school they will deficiency  of intake. Energy that can cause the children quickly experience fatigue and less to concentration for accepting the lesson in the school. Psycomotor test reaction time is the interval between receiving stimulus with a respon do main which includes movement behaviour and physical coordination, motor skills.